Tinjauan Hukum Islam terhadap Pemberian Mahar Non Materi - Yuni Nur Saidah (Faculty of Sharia and Law UNISNU Jepara, 2022)
This study was conducted to discuss the issue of the Provision of Non-Material Dowry in Islamic Law, which in this case was conducted an intensive study in the opinion of the four schools of thought. This study was conducted using a qualitative-library approach by referring to the fiqh literature of each school, which was then analyzed descriptively. The results of this study indicate that the provision of non-material dowries according to the Imam madhhab can be detailed as follows: 1) Abu Hanifah, did not allow it, but from him it was obligatory for a mitsil dowry, 2) Malik, the law initially did not allow it, 3). Imam Shafi'i and Ahmad bin Hanbal allow it.Kajian ini dilakukan untuk mendiskusikan persoalan Pemberian Mahar Non Materi dalam Hukum Islam, yang dalam hal ini dilakukan kajian secara intensif dalam pendapat empat mazhab. Kajian ini dilakukan dengan pendekatan kualitatif-kepustakaan dengan merujuk pada literature Fikih masing-masing mazhab, yang kemudian dilakukan analisis secara deskriptif. Hasil kajian ini menunjukkan bahwa pemberian mahar non materi menurut Imam madzhab dapat dirincikan sebagai berikut: 1)Abu Hanifah, tidak membolehkan, namun darinya wajib mahar mitsil, 2) Malik, hukum awalnya tidak membolehkan, 3). Imam Syafi’i dan Ahmad bin Hanbal membolehkan